Gestión normativa ciudadana: construcción desde la felicidad social y paz en colombia - Chumaceiro Hernández, Nelson Antonio Uribe, Judith J. Hernández de Velazco, Ligia Cielo Romero Marín, Ana Cecilia (Opción, 2020)
En este trabajo se identifican mecanismos y normas vinculados con la gestión ciudadana para la construcción de felicidad social, a partir del proceso de paz en Colombia (2012- julio 2018), mediante revisión bibliográfica, documental y de análisis histórico-conceptual. Como resultado, se evidenció que el desempeño institucional del Estado, del gobierno colombiano, y de la gestión ciudadana, no han sido efectivos para impulsar las prácticas colectivas en la consecución de estos fines, por lo tanto, se concluye: se debe concientizar a los ciudadanos para que gestionen los dispositivos participativos que impulsen la felicidad social y la paz desde las configuraciones preceptivas establecidas. Abstract Social happiness and peace as categories of analysis both in its epistemological construction and in its factual implementation, require review practices and citizens exercises, democratic (formal), that they have promoted peaceful coexistence for purpose of generating higher levels of social welfare, as well as the involved citizen social tissue, which demands the support of legal mechanisms instituted from the State and its Governments. In this order of ideas, in this dissertation the central objective was to identify mechanisms and standards linked with citizen management for the construction of social happiness, from the peace process in Colombia (since 2012-july 2018), through the review of the literature, documentary, and historical, conceptual analysis. As a result, it was evident that the institutional performance of the State, the Colombian Government, and the management citizen, have not been effective to boost the collective practices in the attainment of these goals, Therefore, it is concluded; You must educate citizens so they manage participative devices that encourage social happiness and peace from the established mandatory configurations.